COX24 codes for a mitochondrial protein required for processing of the COX1 transcript - Barros, Mario H. [UNESP]; Myers, Alan M.; Van Driesche, Sarah; Tzagoloff, Alexander (Elsevier, 2006)
In most strains of Saccharomyces cerevisiae the mitochondrial gene COX1, for subunit 1 of cytochrome oxidase, contains multiple exons and introns. Processing of COX1 primary transcript requires accessory proteins factors, some of which are encoded by nuclear genes and others by reading frames residing in some of the introns of the COX1 and COB genes. Here we show that the low molecular weight protein product of open reading frame YLR204W, for which we propose the name COX24, is also involved in processing of COX1 RNA intermediates. The growth defect of cox24 mutants is partially rescued in strains harboring mitochondrial DNA lacking introns. Northern blot analyses of mitochondrial transcripts indicate cox24 null mutants to be blocked in processing of introns aI2 and aI3. The dependence of intron aI3 excision on Cox24p is also supported by the growth properties of the cox24 mutant harboring mitochondrial DNA with different intron compositions. The intermediate phenotype of the cox24 mutant in the background of intronless mitochondrial DNA, however, suggests that in addition to its role in splicing of the COX1 pre-mRNA, Cox24p still has another function. Based on the analysis of a cox14-cox24 double mutant, we propose that the other function of Cox24p is related to translation of the COX1 mRNA. © 2006 by The American Society for Biochemistry and Molecular Biology, Inc.
Keywords: Biochemistry; Enzymes; Genes; Molecular biology; Molecular weight; Mutagenesis; RNA; Yeast; Exons; Introns; Mitochondrial protein; Mutants; Proteins; cyclooxygenase 1; cyclooxygenase 24 enzyme; mitochondrial DNA; mitochondrial protein; unclassified drug; COX24 protein, S cerevisiae; cytochrome c oxidase; epitope; fungal DNA; hemagglutinin; messenger RNA; Saccharomyces cerevisiae protein; controlled study; enzyme localization; intron; molecular cloning; nonhuman; Northern blotting; open reading frame; phenotype; priority journal; protein expression; protein function; protein processing; RNA splicing; Saccharomyces; sequence alignment; yeast; amino acid sequence; biosynthesis; chemistry; enzymology; fungal gene; genetics; metabolism; mitochondrion; molecular genetics; mutation; Saccharomyces cerevisiae; sequence homology; species difference; Amino Acid Sequence; Blotting, Northern; Cloning, Molecular; DNA, Fungal; DNA, Mitochondrial; Electron Transport Complex IV; Epitopes; Genes, Fungal; Hemagglutinins; Mitochondria; Mitochondrial Proteins; Molecular Sequence Data; Mutation; Open Reading Frames; Phenotype; RNA, Messenger; Saccharomyces cerevisiae Proteins; Sequence Homology, Amino Acid; Species Specificity